Turkey - Public Expenditure and Institutional Review : Reforming Budgetary Institutions for Effective Government - World Bank (Washington, DC, 2013)
This Public Expenditure and Institutional Review presents the findings of an analysis of the budget, and institutions of public expenditure management, and accountability, fundamental to policy decisions, and economic management. It builds on extensive analysis undertaken by the Special Ad Hoc Committee on Fiscal Transparency, and Public Finance, and, the review suggests that the current economic crisis is deep-rooted in the institutions of collective decision making in government, confirming that unless fundamental improvements are made to the processes for formulating public policy, allocating resources, and implementing budgets, any economic recovery will almost certainly be fragile, and short-lived. Thus, from the perspectives of system performance, and structural and institutional aspects, an improved budgetary system should enable the government to achieve aggregate fiscal magnitudes, based on expenditures, sustained by tax, and non-tax resources; the budget should generate the adequate information to ensure funding of key policy objectives; and, public accountability should generate incentives to support performance objectives. The report identifies aggregate fiscal management as a major weakness, compromised by the significant growth of off-budget activity, while the weakness of the budget system in terms of ability to support decision-making, is equally pernicious. A series of actions to restore fiscal discipline are outlined for the short-term (2001), and initiatives for a multi-year budget commencing in 2002 are included. Recommendations include strengthening the aggregate fiscal program management capacity; reviving policy formulation capacity, and institutional framework to define budgetary policy; and, initiating budget control devolution, introducing a budget performance approach.